Efficacies of the original and modified WHO-recommended hand rub formulations (2020)
The WHO hand rub formulations have been in use around the world for at least the past ten years. The advent of COVID-19 has further enhanced their use. We reviewed published efficacy data for the original and modified formulations. Only efficacy data according to the European Norms (EN) were found. The bactericidal efficacy of the original formulations was under practical conditions partly insufficient (EN 1500, only effective in 60 s; EN 12791, efficacy too low in 5 min). The 1st modification with higher alcohol concentrations improves their efficacy as hygienic hand rub (effective in 30 s). The 2nd (0.725% glycerol) and 3rd (0.5% glycerol) modification improves their efficacy for surgical hand preparation (effective in 5 and 3 min). The original and 2nd modified formulations were tested and demonstrate activity against enveloped viruses including SARS-CoV-2 in 30 s. The ethanol-based formulation is also active against some non-enveloped test viruses in 60 s (suspension tests, EN 14476). In vivo data of the formulations would provide a more reliable result on the virucidal efficacy on contaminated hands but are currently not available. Nevertheless, the last modifications should be adopted for use in healthcare.